The Effect of Place Attachment on Pro-environment Behavioral Intentions of Visitors to Coastal Natural Area Tourist Destinations. (November 2015) - Tonge, Joanna; Ryan, Maria M.; Moore, Susan A.; Beckley, Lynnath E.
It has been hypothesized that as individuals become attached to a place, they are more likely to protect that place. Managers of natural area tourism destinations may be able to use this relationship to assist in sustainably managing such places. An on-site visitor survey was administered at Ningaloo Marine Park, Australia, to examine the effect of a multi-dimensional place attachment construct on pro-environment behavioral intentions. The behaviors encompassed three categories based on the perceived level of commitment and where the behaviors physically occurred. They included on-site actions by visitors, visitors telling others how to act on-site, and off-site actions to conserve the Marine Park. Structural equation modeling revealed place identity directly affecting all three behavioral categories, the effect increasing with the level of commitment required to undertake the pro-environment behaviors. This suggests that a sophisticated understanding of place identity is essential for the management of natural area tourism destinations.